ANALISIS KINERJA SIM e-SPTPD MENGGUNAKAN METODE PIECES DI BADAN PENDAPATAN DAERAH KABUPATEN GORONTALO - Wahab, Fatma; Katili, Muhammad Rifai; Zakaria, Alfian (Diffusion: Journal of Systems and Information Technology, 2024)
Operated in finance and public services, the Regional Agency of Gorontalo Regency conducts local taxcollection activities, including tax reporting and payment. In the reporting process, the Regional RevenueAgency of Gorontalo Regency develops and applies the regional tax payment and reporting system throughonline-based information technology or SIM e-SPTPD. During the implementation, the users sometimesencounter several obstacles, such as a slow system, inconsistent data (missing data), and users who areilliterate about the system. Therefore, this study aimed to determine the influence of user perception on thesuccess of SIM e-SPTPD performance using the PIECES method with six independent variables(Information, Economy, Control, Efficiency, and Service), one dependent variable (Performance), andother variables related to SIM e-SPTPD performance. The study was conducted on 40 respondents whoused SIM e-SPTPD. Data in this study were collected through observation, interview, and questionnairemethods, which were then processed using multiple linear regression to test the hypothesis. From the study,the Information, Economy, and Efficiency variables positively influence the Performance variable.Meanwhile, Control and Service variables have a negative influence on Performance variables. Partially,the Information, Economy, and Efficiency variables influence the Performance variables, and the Controland Sevice were otherwise. In contrast, the variables mentioned did not influence the Performance variablesimultaneously.